Analisis Pengendalian Internal Atas Persediaan Obat pada Dinas Kesehatan Kabupaten Sikka - Antonius Narang Eong; Maria Nona Dince; Emilianus Eo Kutu Goo; Marselus Don Bosko (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to analyze internal control over drug inventory at the Sikka District Health Office. The method used in this study is a qualitative descriptive method, the sample in this study is the Pharmacist section at the Sikka District Health Office. The data collection method in this study is interviews and documentation which are then analyzed using the Miles and Huberman theory and adjusted to the existing data. The results of this study indicate that at the Sikka District Health Office, the use of SOPs for controlling drug inventory shows a commitment to creating a healthy control environment. The Sikka District Health Office has emphasized the importance of creating Standard Operating Procedures (SOPs) for all stages of drug inventory control from planning to recording and reporting. This shows a commitment to ensuring that the drug inventory management process is carried out in a structured and efficient manner, with detailed SOPs for each step. In the field of Supervision, Monitoring of drugs in relation to the internal control system at the Sikka District Health Office is carried out through monthly stock opname by checking the conformity between stock cards, physical goods, and reporting. This process reflects an effort to regularly monitor and evaluate the condition of drug inventory. The Sikka District Health Office can identify any discrepancies or inconsistencies that may indicate problems in inventory management. This step allows them to immediately take necessary corrective actions, such as further investigation or inventory adjustments, to ensure that drug inventory remains well-managed and accurate.